Noradrenergic Responsiveness Supports Selective Attention across the Adult Lifespan - Dahl, Martin J.; Mather, Mara; Sander, Myriam C.; Werkle-Bergner, Markus (The Journal of neuroscience, 2020)
Selectively attending to relevant information while blocking out distractors is crucial for goal-directed behavior, yet with advancing age, deficits emerge in attentional selectivity. Decrements in attention have been associated with altered noradrenergic activity in animals. However, research linking noradrenergic functioning to attention in aging humans is scarce, likely reflecting long-standing methodological challenges in noninvasive assessments. We studied whether age-related differences in the noradrenergic system predict differences in attention. We measured pupil dilation, a noninvasive marker of arousal-related norepinephrine (NE) release, while concurrently recording the EEG of male younger ( N = 39; 25.2 ± 3.2 years) and older adults ( N = 38; 70.6 ± 2.7 years). Arousal was modulated on a trial-by-trial basis using fear-conditioned (CS + ) stimuli. During conditioning, pupil and EEG markers related to heightened arousal were identified. Afterward, in a dichotic listening task, participants were cued to direct attention to either the left or right ear while highly similar syllable pairs were presented simultaneously to both ears. During the dichotic listening task, presentation of fear-conditioned stimuli reinstated the acquired arousal response, as reflected in pupil and EEG α-β band responses. Critically, pupil dilation to CS + was correlated with stronger EEG α-β desynchronization, suggesting a common dependence on NE release. On a behavioral level, stronger arousal reactions were associated with better attention. In particular, structural equation modeling revealed that the responsiveness of the NE system is associated with attention on a latent construct level, measured by several indicator tasks. Overall, our results suggest that the responsiveness of the NE system supports attention across the lifespan. SIGNIFICANCE STATEMENT In old age, the ability to selectively process relevant aspects of the environment fades. Animal research suggests that the neuromodulator norepinephrine helps to maintain selective attention. We tested younger and older adults across a variety of attention tasks. In addition, we used arousing stimuli to experimentally activate participants' noradrenergic system while recording pupillometry and EEG to infer its functional capacity. Older adults showed compromised attention and reduced noradrenergic responsiveness as indicated by interrelated pupil and EEG markers. Crucially, in both age groups, a more responsive noradrenergic system was strongly associated with attention. Our findings link animal and human studies on the neural underpinning of attention in aging and underscore the importance of the noradrenergic system in late-life cognition.